(untitled) (Bangladesh Journal of Child Health, 2016)
Background: Portal hypertension is defined by a pathological increase in portal venous pressure. Any condition that interfere with blood flow at any level within the portal system can lead to portal hypertension. For better management, it is important to determine the underlying cause. Objective: To evaluate the etiology of portal hypertension in children admitted in a tertiary care centre of Bangladesh. Materials & Methods: This cross sectional study was done in the Department of Pediatric Gastroenterology, Hepatology & Nutrition, Dhaka Shishu (Children) Hospital, Dhaka, Bangladesh on 40 consecutive cases of portal hypertension enrolled from April 2014 to March 2015. Results: Age of the children was 2-12 years with mean age of 7.2±4.3 years and male:female ratio was 1.5:1. Out of 40 children, 32 (80%) developed portal hypertension due to pre-hepatic causes and 8 (20%) hepatic causes. In pre-hepatic causes of portal hypertension, out of 32 children, portal vein thrombosis was found in 20 (62.5%) cases, splenic vein thrombosis in 4 (12.5%) & 8 (25%) were idiopathic. On the other hand hepatic causes of portal hypertension, out of 8 children, cryptogenic was found in 4 (50%) cases, wilsons disease, chronic hepatitis B virus infection, biliary cirrhosis & autoimmune hepatitis each was found in 1 (12.5%) case. In pre-hepatic cases first variceal bleed much earlier than hepatic cases (4.4±3.6 Vs 7.6±4.6 years). Conclusion: Extra-hepatic diseases were the most common etiology of portal hypertension in studied children. Portal venous thrombosis in extra-hepatic cases & cryptogenic liver disease in intra-hepatic cases were the most common causes Bangladesh J Child Health 2015; VOL 39 (1) :14-17